BREAKFAST HABIT AND ACADEMIC PERFORMANCE AMONG SUBURBAN ELEMENTARY SCHOOL CHILDREN - Widyanti, Putu Ayu; Sidiartha, I Gst Lanang (Medicina; Vol 44 No 1 (2013): Januari 2013, 2013)
Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 Academic performance is affected by a numbers of factors. Age, gender, nutritional status, and breakfast habits are some factors that have relation with academic performance. Nutritional statues among school children still to be concerned. Breakfast habit is important thing to do before school to maintain enough calories to study and work well. The aim of this study was to determine the association of breakfast habits and academic performance especially in suburban elementary school children. An analytic cross sectional study conducted in children aged 6-12 years who studied at SD 1 Taro, Gianyar regency, Bali. There were 178 students participated in this study. We found 3 factors associated with academic performance i.e. breakfast, gender , and age with OR=2.56 (95% CI 1.16 to 5.66), P=0.02; OR=0.32 (95% CI 0.15 to 0.70), P=0.04; OR=6.52 (95% CI 2.73 to 15.53), P<0.0001, respectively. We conclude there was an association between breakfast habits and academic performance. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: academic performance, breakfast habits, school age children